2019
DOI: 10.3892/ijmm.2019.4073
|View full text |Cite
|
Sign up to set email alerts
|

miR‑335 promotes stress granule formation to inhibit apoptosis by targeting ROCK2 in acute ischemic stroke

Abstract: Under harmful environmental conditions, stress granules (SGs), macromolecular aggregates that are associated with cell survival and death, are produced in the eukaryotic cytoplasm. However, whether and how microRNAs (miRNAs/miRs) modulate SG formation induced by acute ischemic stroke has not been investigated. In the present study, a rat model of middle cerebral artery occlusion (MCAO) was utilized and miRNA array profiling and reverse transcription-quantitative polymerase chain reaction were performed. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…*P value < 0.05; ***P value < 0.001; ****P value < 0.0001. in the oxygen-glucose deprivation of PC12 cells using doublelabeled immunofluorescence (TIA1 and G3BP1). In our previous publication we showed that SG formation may reduce ischemic cortical injury in the early stage of AIS (Si et al, 2019). Therefore, our in vitro and in vivo experimental results suggested that METTL3-mediated SG formation might reduce AIS injury in the early stage of the disease.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…*P value < 0.05; ***P value < 0.001; ****P value < 0.0001. in the oxygen-glucose deprivation of PC12 cells using doublelabeled immunofluorescence (TIA1 and G3BP1). In our previous publication we showed that SG formation may reduce ischemic cortical injury in the early stage of AIS (Si et al, 2019). Therefore, our in vitro and in vivo experimental results suggested that METTL3-mediated SG formation might reduce AIS injury in the early stage of the disease.…”
Section: Discussionmentioning
confidence: 50%
“…A total of 108 male Sprague-Dawley (SD: 230-260 g; 8-9-weeks old) rats were randomly divided into six groups (n = 18 rats/group): the sham group (sham operation); R-0 h group (MCAO for 2 h and reperfusion for 0 h); R-6 h group (MCAO for 2 h and reperfusion for 6 h); R-12 h group (MCAO for 2 h and reperfusion for 12 h); R-18 h group (MCAO for 2 h and reperfusion for 18 h); and R-24 h group (MCAO for 2 h and reperfusion for 24 h). The MCAO model was established as previously described (Si et al, 2019). Briefly, after a median incision on the neck, the left common carotid artery (CCA), internal carotid artery (ICA), and external carotid artery (ECA) were isolated.…”
Section: Experimental Animals and Mcao Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that SGs formation and ischemia-reperfusion onset may occur concurrently in principle because of the similarity in the two events ( Lee and Seydoux, 2019 ; Wolozin and Ivanov, 2019 ). Our previous research demonstrates that the marker of stress granules [T-cell intracellular antigen 1 (TIA1)] is upregulated at the early time-points of blood reperfusion after 2 h of cerebral ischemia, accompanying a significant decrease of apoptosis level in the ischemic cortex ( Si et al, 2019 ). This finding hint that SGs formation may occur in the early state of AIS, but the direct evidence is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…AIS triggers a damaging cascade as a multifactorial disease, including endoplasmic reticulum (ER) stress, oxidative stresses, excitotoxicity, inflammation, and apoptosis ( Bettencourt and Ferro, 2020 ; Sui and Gao, 2020 ). Notably, ischemic cascade conditions exhibit very similar characteristics to stress granules (SGs) formation ( Si et al, 2019 ). Stress granules are stalled translational aggregates generated in the cytoplasm and induced by varied environmental stress, including heat shock, hypoxia, ER stress, and oxidative stress ( An et al, 2019 ; Guzikowski et al, 2019 ; Ivanov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%